Introduction to Paremiology. A Comprehensive Guide to Proverb Studies - Varga, Melita Aleksa (De Gruyter, 2014)
This handbook introduces key elements of the philological research area called paremiology (the study of proverbs). It presents the main subject area as well as the current status of paremiological research. The basic notions, among others, include defining proverbs, main proverb features, origin, collecting and categorization of proverbs. Each chapter is written by a leading scholar-specialist in their area of proverbial research. Since the book represents a measured balance between the popular and scientific approach, it is recommended to a wide readership including experienced and budding scholars, students of linguistics, as well as other professionals interested in the study of proverbs.